Fe6 clusters of tripodal alcohol ligands: Synthesis, structures and magnetostructural properties. (1st May 2019) - Ashafaq, Mo; Khalid, Mohd; Raizada, Mukul; Ali, Anzar; Faizan, Mohd; Shahid, M.; Ahmad, Musheer
Graphical abstract: Two μ 6 -oxo centered Fe6 clusters, (NEt3 H)2 [Fe III 6 Cl6 (µ6 -O)(thme)4 ]·3(H2 O)2 (1 ) and (NEt3 H)2 [Fe III 6 Cl6 (µ6 -O)(thmp)4 ]·5.5(H2 O) (2 ), were synthesised and characterized crystallographically. The fascinating features of the non-covalent interactions have been explored and corroborated theoretically by Hirshfeld surface analysis. A magnetic investigation for1 and2 indicates the presence of dominant antiferromagnetic interactions. Abstract: The synthesis, crystal structures, cyclic voltammetric and magnetic characterization of (NEt3 H)2 [Fe III 6 Cl6 (µ6 -O)(thme)4 ]·3(H2 O) (1 ) (H3 thme = trishydroxymethyl ethane) and (NEt3 H)2 [Fe III 6 Cl6 (µ6 -O)(thmp)4 ]·5.5(H2 O) (2 ) (H3 thmp = trishydroxymethyl propane) are reported. Both complexes crystallized in the orthorhombic system and have the space group Pca 21. The metallic cores of the complexes comprise of the [(μ6 -O)Fe6 (μ-O)12 ] unit. The ligands thme 3− and thmp 3− adopt the same η 2, η 2, η 2, µ3 -bridging mode of the alkoxide oxygen atoms in1 and2 . Electrochemical studies are consistent with formation of stable quasi-reversible one electron Fe II/III redox couples in solution. The fascinating features of the non-covalent supramolecular contacts have been explored and corroborated theoretically by Hirshfeld surface analysis along with electrostatic potential (ESP), deformation density (DD) and ab initio calculations. The interplay of the interactions, (i.e., H⋯O, Cl⋯H and other contacts) give rise to the consolidation of discrete units of1 and2 into supramolecular architectures. Variable-temperature and field ( H ) solid-state direct and alternating current magnetic susceptibility measurements were done on samples of1 and2 in the temperature range 1.8–300 K. Analysis of the data confirmed the presence of dominant antiferromagnetic interactions, leading to an S = 0 ground state, and no out of phase ac magnetic susceptibility signals were observed for either cluster, ruling out single-molecule magnet behaviour.